Conformal spatiotemporal modulation enabled geometric frequency combs - Wu, Haotian (2024)
The interaction between light and the time-varying medium exhibits non-Hermitian characteristics, leading to intriguing phenomena, such as parametric amplification, momentum gaps, and temporal refraction. In this study, we introduce the concept of the conformally evolved spatiotemporal modulation, where the space- and time-dependent permittivity function ϵ (x,t) undergoes rescaling over time, i.e., ϵ (x,t + Δt) = ϵ (sx,st). In such systems, spatiotemporal interfaces are no longer modulated at a uniform speed, enabling us to generate a special type of geometric optical comb with exponentially distributed frequency spacing under monochromatic incidence. Compared with traditional linear frequency combs, these optical combs exhibit several distinct properties. First, the excitation of geometric harmonics can drastically amplify the output signal through cascade field enhancement with the appropriate modulation speeds. Second, the designed geometric comb showcases a significant reduction of ambiguous peaks in the autocorrelation, resulting in suppression of reverberation and resolution enhancement for radar detections.